Correction: On the environmental competitiveness of sodium-ion batteries under a full life cycle perspective – a cell-chemistry specific modelling approach. Issue 2 (15th December 2021) - Peters, Jens F.; Baumann, Manuel; Binder, Joachim R.; Weil, Marcel
Abstract : Correction for 'On the environmental competitiveness of sodium-ion batteries under a full life cycle perspective – a cell-chemistry specific modelling approach' by Jens F. Peters et al., Sustainable Energy Fuels, 2021, 5, 6414–6429, DOI: ; 10.1039/D1SE01292D .